Analisis Kejadian Stunting di UPT Puskesmas Tebing Bulang Kabupaten Musi Banyuasin - Asnandi, Asnandi; Gustina, Erma; Zaman, Chairil (Universitas Baiturrahim, 2024)
The global prevalence of stunting is classified as high because it is between 20% - <30%. According to the Indonesian Ministry of Health from Basic Health Research (Riskesdas) in 2018, the prevalence of underweight, stunting, wasting respectively was 17.8%; 30.8 percent; and 10.24%. This research aims to determine the picture of stunting incidents at the Tebing Bulang Community Health Center. This research itself is quantitative in nature using an analytical survey method with a cross sectional approach. The research was conducted at the Tebing Bulang Community Health Center targeting toddlers aged 1 - 5 years using a sampling technique, namely simple random sampling technique. The number of samples is 94 samples. The time for conducting the research was from February to April 2024. The results of the study showed that there was a relationship between exclusive breastfeeding and the incidence of stunting. There was no relationship between a history of IMD and the incidence of stunting. There was a relationship between a history of giving MP-ASI and the incidence of stunting. There was no high correlation. mother's body and the incidence of stunting, there is a relationship between the educational status of the mother and the incidence of stunting, there is a relationship between family income status and the incidence of stunting, there is a relationship between the history of LBW and the incidence of stunting, there is a relationship between the history of infection and the incidence of stunting. It is hoped that the community health center will be able to coordinate with related cross-sectors to provide assistance to families who have toddlers with stunting so that it is hoped that the assistance can improve the nutritional quality of children affected by stunting..